Carbohydrates and total carotenoids in two varieties of mangarito - Ferreira, Ana Paula Sato; Puiatti, Mário; Pereira, Ariana Mota; Cecon, Paulo Roberto; Bhering, Aline da Silva; Mendes, Teresa Drummond Correia (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the composition of carbohydrates and carotenoids in mother rhizomes and small cormels of the dwarf and giant mangarito (Xanthosoma riedelianum) varieties. Rhizome samples collected during the crop cycle and 90 days after storage were evaluated for carbohydrate and total carotenoid contents. Rhizomes showed an increase in the carbohydrate content, and the mother rhizome of the dwarf variety had linear increases in the carotenoid content, during cultivation. Storage reduces carbohydrate and total carotenoid contents in all rhizomes.